Assessment of Supply Chain Management Practices and Sustainable Food Security in Nigeria - Olawale Gazal Hammed (Logistic and Operation Management Research (LOMR), 2022)
Supply chain flow is a major concern for food security, particularly to ensure that food is not lost between farmers and consumers. Food security has become a highly emotive issue, as chronic hunger, local food shortages, and sudden increases in food prices are strongly influencing public sentiment and reaction. This raises concern for the assessment of supply chain management and sustainable food security in Nigeria, using honesty among supply chain participants, effective storage facilities, and quality of seed as a determinant for sustainable food security. A survey research design was adopted for this study, using a structured questionnaire. Convenient and Purposive sampling techniques were used to select 80 farmers from the North-Western state of Nigeria. Descriptive statistics were used to analyse the data collected, which was presented using charts. The findings of this study show that honesty among supply chain participants, effective storage facilities for farm produce, and the quality of seeds to plant will enhance nutritional foods in society, promotes both affordability and high profits for all participants in the supply chain based on the response of the selected farmers. It was further revealed from the study that Government intervention in terms of subsidy and credit facilities to the farmers are not well harnessed by the real farmers that are actually in the business of farming. Therefore, it was recommended, among others, that there should be an effective feedback mechanism from the government to ensure the subsidy is actually addressing the purpose of its establishment.